Variation of Triterpenoid Saponin Content in Platycodon grandiflorum (Jacq.) A.D.C. - Yan, Y.Z.; Xue, J.C.; Wu, J.R.; Yoo, D.S.; Lee, S.Y.; Kim, Y.K.; Uddin, M.R.; Park, S.U. (Asian Journal of Chemistry, 2011)
In this study, the accessions of the balloon flower (Platycodon grandiflorum) were characterized using petal colour and geographical location to determine saponin variability. Based on differences in saponin levels, the accessions with blue flowers dominated over those with white flowers for this species. Accession CB01 with blue flowers contained the highest amount of platycoside E and platycodin D3, whereas accession CB02 with the same coloured flower contained the highest amount of platyconic acid and platycodin D. Accession KW01 with white flowers contained the highest amount of Deapio-Platycoside E, platyconic acid, platycodin D2 and platycodin D. Among the accessions studied the CB01 and CB02 accessions might be considered as potential accessions in terms of saponin contents.